PRINCIPLES OF ORGANIZING SMALL ARCHITECTURAL FORMS IN NATIONAL STYLE IN ARCHITECTURE AND LANDSCAPE DESIGN - Daminova Umida Olimovna (European Science Publishing, 2025)
Today, it is worth noting that the styles applied in global architecture and landscape design are primarily suited for European countries. However, our homeland, Uzbekistan, is rich in national traditions and customs, and this beautiful heritage, which has become a cherished tradition, should be reflected in our architecture and landscape design. To preserve our heritage in architecture and landscape design, it is essential to provide as much knowledge as possible to the younger generation of architects studying at higher education institutions. It should be emphasized that to create our gardens in a national style, we can organize landscape design not only with plants but also with small architectural forms.
Keywords: Small architectural form, landscape, minimalism, decorative compositions, project.